Association Between Cardiometabolic Multimorbidity and 15-year Mortality in the Asia Cohort Consortium - Sangjun Lee; Choonghyun Ahn; Sarah Krull Abe; Md Shafiur Rahman; Md Rashedul Islam; Eiko Saito; Seokyung An; Norie Sawada; Xiao-Ou Shu; Woon-Puay Koh; Hui Cai; Atsushi Hozawa; et al. (Journal of Epidemiology, 2025)
Background: Studies on the association between multimorbidity and mortality in large populations have mainly been conducted in European and North American populations. This study aimed to identify the association between cardiometabolic multimorbidity and all-cause and cardiovascular disease (CVD) mortality in the Asia Cohort Consortium. Methods: In this prospective cohort study, pooled analysis was performed to evaluate the association between cardiometabolic diseases (hypertension, diabetes, ischemic heart disease, and stroke), multimorbidity, and all-cause and CVD mortality, including premature mortality, among participants from 11 Asian cohort studies. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox hazard regression. Results: A total of 483,532 participants were followed for a median of 14.3 years. Compared with participants without any disease, those with stroke and diabetes had higher age- and sex-adjusted HRs for all-cause mortality (HR 3.9; 95% CI, 3.28–4.56). Moreover, the age- and sex-adjusted HRs for CVD mortality were highest in participants with stroke, ischemic heart disease, and diabetes (HR 10.6; 95% CI, 6.16–18.25). These patterns remained consistent after additional adjustments for smoking status and body mass index. The risk of premature mortality followed similar trends but was more pronounced. Conclusion: These findings highlight the differential impacts of individual cardiometabolic diseases and their combinations on mortality risks. Stroke and diabetes were associated with the highest risks for all-cause and cardiovascular mortality, underscoring the need for targeted prevention and personalized management strategies tailored to these high-risk conditions in Asian populations.